1997
DOI: 10.1073/pnas.94.21.11221
|View full text |Cite
|
Sign up to set email alerts
|

Recombination activities of HsDmc1 protein, the meiotic human homolog of RecA protein

Abstract: Meiosis-specific homologs of RecA protein have been identified in Saccharomyces cerevisiae and higher eukaryotes including mammals, but their enzymatic activities have not been described. We have purified the human protein HsDmc1 produced in Escherichia coli from a cloned copy of the cDNA. The recombinant enzyme had DNA-dependent ATPase activity with an estimated k cat of 1.5 min ؊1 . DNase protection experiments with oligonucleotides as substrates indicated that HsDmc1 protein binds preferentially to single-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
116
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(125 citation statements)
references
References 41 publications
6
116
1
Order By: Relevance
“…Thus, a large number of sequencing reads containing long ITRs can be found in the sequencing libraries prepared from meiotic cells. These reads were derived from DNA fragments that preferentially interact with DMC1 and RAD51, both known to bind ssDNA (Sung 1994;Li et al 1997). These data are thus consistent with ssDNA recovery via a hairpin-mediated mechanism.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Thus, a large number of sequencing reads containing long ITRs can be found in the sequencing libraries prepared from meiotic cells. These reads were derived from DNA fragments that preferentially interact with DMC1 and RAD51, both known to bind ssDNA (Sung 1994;Li et al 1997). These data are thus consistent with ssDNA recovery via a hairpin-mediated mechanism.…”
Section: Resultssupporting
confidence: 70%
“…One can imagine further applications where the ability of our approach to distinguish single-stranded and double-stranded substrates would be beneficial. It may, for example, allow us to differentiate ssDNA and dsDNA targets of proteins that can bind both ssDNA and dsDNA, such as RAD51, DMC1, or Smc5 (Sung 1994;Li et al 1997;Roy et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Dmc1 was also proposed to be a structural and functional relative of RecA based on mutant and sequence analysis (Bishop et al 1992;Story et al 1993). Biochemical demonstration of recombinase activity for Rad51 and Dmc1 supports the idea that each protein promotes strand exchange by a mechanism related to that of RecA (Sung 1994;Baumann et al 1996;Li et al 1997;Masson et al 1999;Hong et al 2001). Although similar in several respects, electron microscopy (EM) analysis showed that Dmc1 and Rad51 differ in that Dmc1 has a strong tendency to form tori and can bind DNA in the toroid form Passy et al 1999;Kinebuchi et al 2004).…”
mentioning
confidence: 95%
“…The molecular activities of RAD51 and DMC1 proteins have been studied in depth in vitro. Both proteins form helical structures on ssDNA and mediate the invasion of those so-called presynaptic filaments into homologous duplex DNA to form displacement loops (Shinohara et al, 1992;Ogawa et al, 1993;Benson et al, 1994;Sung, 1994;Baumann et al, 1996;Li et al, 1997;Masson et al, 1999;Hong et al, 2001;Sehorn et al, 2004;Yu and Egelman, 2010). Although similar in structure, some differences between the two recombinases may exist.…”
Section: Introductionmentioning
confidence: 99%